Meinrad Greiner, Laws and Ordinances, Ordained and Established by the Mayor, Aldermen, and Commonalty, of the City of New-York, in Common Council Convened for the Good Rule and Government of the Inhabitants and Residents of the Said City Second Edition, at 25-26, A Law to regulate the keeping of gun-powder in the city of New York (1799) - (:unkn) unknown (General Publisher, 1799)
That no person or persons shall keep in any house, shop store house or other place within two miles of the city hall of the said city (Magazines of powder of the United States or of this state only excepted) any more or greater quantity of gun powder at one time than twenty-eight pounds,
--
Keywords: GUN POWDER STORAGE